The Shikhara of the Shiva Temple (Temple 3) - Temples of India Project Team (Jio Institute, 2024)
The shikhara (superstructure) of the garbhagriha (sanctum sanctorum) of the Shiva Temple (Temple 3) is severely damaged, but remains of the mulamajari (central or main spire) can still be seen, carved with the jala of miniature gavaksha (dormer window) motif. The karnaratha (decorative pilasters) of the present superstructure shows five bhumis (tiers), and the arrangement of the anga shikhara (minor spires) can be seen just above the varandikas (moulded parapet).